New Culture Medium to Xanthan Production by Xanthomonas campestris pv. campestris - Rodrigues Carignatto, Cintia Regina [UNESP]; Mustafe Oliveira, Kassandra Sussi [UNESP]; Gomes de Lima, Valeria Marta [UNESP]; Oliva Neto, Pedro de [UNESP] (Springer, 2011)
Xanthan is a important biopolymer for commercial purpose and it is produced in two stages by Xanthomonas campestris. In the first one, the bacterium is cultivated in the complex medium enriched in nitrogen and the biomass produced is used as inoculum for the next stage in which the gum is produced in another medium. In this work a new medium for the first stage is proposed in place of currently used YM medium. Different formulated growth media were studied and the correspondent biomass produced was analysed as inoculum for the second stage. The inoculum and gum were produced by batch process in shaker at 27A degrees C in pH 6.0 and at 30A degrees C in pH 7.0, respectively. The gum was precipitated with ethanol (3:1 v/v). The dryed biomass and xathan gum produced were determined by drying in oven at 105 and 40A degrees C, respectively. The viscosity of the fermentation broth and 1% gum solution in water were determined in Brookfield viscometer. The formulated medium presented the increase in gum production (30%), broth (136%) and 1% gum solution viscosity (60%) compared to YM, besides the inferior cost. The results showed the importance of the quality of the inoculum from the first stage of the culture which influenced on the gum viscosity in the second stage.
Keywords: Development; Growth medium; Xanthomonas campestris; Xanthan; Viscosity